Comparison of the Factors Affecting Smile Esthetics with the Patient and Physician Perceptions Using the Smile Esthetic Index - Özkan Şen, Dilek; Taştan Eroğlu,, Zeynep; Babayiğit,, Osman; Uçan Yarkaç, Fatma (Journal of Dentistry Indonesia, 2024)
Objective: This study aimed to evaluate the smile esthetics of individuals and the factors affecting it using the smile esthetic index (SEI) and compare them with the patient’s perception of smile. Methods: Seventy-six patients consisting of 44 females and 32 males who presented to for routine periodontal treatments were included in study. The smile esthetics were evaluated by three researchers on the photographs taken from the patients. The visual analog scala was used for the subjective evaluation of smile esthetics. Results: According to the results obtained from the study, the average of the SEI total scores was 6.38; the mean subjective evaluation of smile aesthetics was 6.33. There was no statistically significant difference depending on gender and age in the subjective and objective evaluations of the patients’ smile aesthetics. A statistically significant correlation was found between the physician’s scoring for objective smile aesthetics and the age of the patients. Conclusion: The SEI is an index that can be applied in the clinic and is used to evaluate the smile esthetics revealing objective values. Different esthetical outcomes may occur with objective and subjective evaluation.The use of these indices for diagnosis and treatment planning will allow for developing appropriate treatments.